2009
DOI: 10.1111/igc.0b013e3181a388c4
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Mediated Immune Responses to Human Papillomavirus 16 E6 and E7 Antigens as Measured by Interferon Gamma Enzyme-Linked Immunospot in Women With Cleared or Persistent Human Papillomavirus Infection

Abstract: Cell mediated immune responses have been thought to be important in the control of HPV infections. We examined cell-mediated immune responses to HPV 16 E6 and E7 in the peripheral blood using IFN-γ enzyme-linked ImmunoSpot (ELISpot) assay in women with HPV 16 infection who showed clearance and compared these women to women with HPV 16 persistence. Women participating in a longitudinal study of cervical HPV were recruited once cervical HPV 16 infection was detected by PCR. Four groups of women were examined; 1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
63
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 21 publications
1
63
0
Order By: Relevance
“…HPV infection of the lower genital tract and its outcome are influenced by host immune response, virulence of the HPV, smoking and immunosuppression (Duong and Flowers, 2007;Sherman et al, 2008). Successful adaptive immune responses that lead to clearance of genital HPV infection are believed to be mediated by local T cell-mediated immunity (Farhat et al, 2009). The virus life cycle and several immune evasion mechanisms limit virus-specific immunity, facilitating persistent infection and the increased risk of carcinogenesis (Stern, 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…HPV infection of the lower genital tract and its outcome are influenced by host immune response, virulence of the HPV, smoking and immunosuppression (Duong and Flowers, 2007;Sherman et al, 2008). Successful adaptive immune responses that lead to clearance of genital HPV infection are believed to be mediated by local T cell-mediated immunity (Farhat et al, 2009). The virus life cycle and several immune evasion mechanisms limit virus-specific immunity, facilitating persistent infection and the increased risk of carcinogenesis (Stern, 2005).…”
mentioning
confidence: 99%
“…The virus life cycle and several immune evasion mechanisms limit virus-specific immunity, facilitating persistent infection and the increased risk of carcinogenesis (Stern, 2005). Indeed, it has been shown that patients with persistent HPV infection have depleted T-cell responses against the viral early gene products E2 and E6 measured systemically (de Jong et al, 2004;Farhat et al, 2009). In addition, T regulatory cells are negative regulators of otherwise useful anti-tumour T-cell immunity and locally increased levels have been implicated in the persistence of both cervical and vulval HPVassociated lesions (van der Burg et al, 2007;Winters et al, 2008).…”
mentioning
confidence: 99%
“…A T-cell-mediated immune response against HPV antigens is important in controlling progression to CIN by sustaining viral clearance (31). The systemic and local reactions induced by GTL001 were consistent with the pharmacologic effects of a vaccine inducing a T-cell response.…”
Section: Cellular Immunogenicity Cellular Immunogenicity Was Assessementioning
confidence: 53%
“…Cervicovaginal lavage (CVL) samples were collected at 4-to 6-month intervals from women participating in an ongoing study of the natural history of HPV infection in adolescents described elsewhere (19). All participants provided informed consent according to the guidelines set forth by the committee for human research, University of California, San Francisco.…”
Section: Methodsmentioning
confidence: 99%